Real-World Outcomes and Critical Thinking: Differential Analysis by Academic Major and Gender. - Franco, Amanda; da Silva Almeida, Leandro (Paideia (0103863X))
The Real-World Outcomes is an inventory that measures everyday problematic behaviors that represent decisions where critical thinking is presumably absent; assessing the negative outcomes of poor daily decisions helps to infer the degree of critical thinking that mediates everyday reasoning. In the present paper, we describe the process of translation and cultural adaptation of this inventory to Portuguese. We present evidence of its administration to 259 college students concerning reliability, and differences based on academic major and gender. No statistically significant differences were found, either due to academic major or gender. Results suggest the value of this instrument to assessing daily decision making and life outcomes, and also, to estimate the quality of critical thinking in everyday life.